The Effect of Destination Image and Safety on Tourists' Decisions to Visit Nipah Beach After A Robbery Incident - Ismianti, Fitria; Athar, Handry Sudiartha (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of destination image and safety on tourists' decisions to visit Nipah Beach. Data collection methods used questionnaires. The population consisted of 100 respondents, with a sample size of 100. The analysis method used in this study was multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that, first, destination image and safety have a positive and significant effect on the decision to visit. The results of this study are expected to be taken into consideration by tourism managers and local governments in determining the right strategy to restore the image of Nipah as a destination and improve safety aspects in order to attract tourists to visit.